Kosmos, kerk en eschaton: In gesprek met Flip Theron - Conradie, EM (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
Cosmos, church and eschaton: in conversation with Flip Theron This article enters into a conversation with Flip Theron, a former professor of systematic theology at Stellenbosch University, regarding his views on the relationship between cosmos, church and eschaton. The first section offers a brief summary of Theron’s position, based especially on his doctoral dissertation. The second section raises a number of questions on the theological roots of his views on the church as paroikia. A third section continues the conversation by exploring the theological dangers of docetism, Manicheism and gnosticism.